MICROSTRUCTURE OF NiCrBSi/WC COMPOSITE COATING DEPOSITED ON AISI316 STAINLESS STEEL BY TIG COATING PROCESS - Buytoz, S.; Kok, M.; Qader, I. N.; Balci, E.; Dagdelen, F. (World Scientific Publ Co Pte Ltd, 2021)
It is aimed to investigate the coating of AISI316 stainless steel with NiCrBSi/WC at different ratios using TIG method. In this study, the Ni-based WC-reinforced MMC layer was manufactured by the TIG composite coating method, and then the microstructure of the coating layer was examined. Microstructure and phase components of the composite coatings were characterized by optical microscopy, scanning electron microscopy, and X-ray diffraction. A metallurgic bound was found between the coating layer and the substrate through the TIG coating process. WC was re-solidified in the matrix by dissolving with high input energy. Several phases were found, including Ni-rich (gamma-Ni) primary dendritic phase, Ni-Ni3B, and Ni3Si eutectic structure, Cr7C3, Cr2B3, Cr3Ni2, Ni2W4C, and Ni17W(3) phases in dendritic structures. The presence of carbides in the structure had affected the hardness of the coating. The maximum hardness value was found to be 469.5 HV and the hardness of the coating layers was increased at least 2.5 times compared to that of the substrate material.
Keywords: AISI316 stainless steel; NiCrBSi/WC; TIG coating; microstructure; Cr7C3